nalyzing Trust, Satisfaction, and Loyalty Dynamics: A Study of BNI Bank's Savings Customer Relationships in the Banking Sector - Wifaq Adiputera (IHSA Institute, 2023)
This research delves into the intricate interplay between trust, satisfaction, and loyalty among BNI Bank's savings customers, aiming to unravel the underlying factors shaping customer-bank relationships. Employing a mixed-methods approach, the study combines quantitative surveys and qualitative inquiries to explore the multifaceted dimensions influencing customer perceptions and behaviors. Quantitative analyses reveal a robust positive correlation between trust and satisfaction levels, highlighting the pivotal role trust plays in shaping contentment with BNI Bank's services. Furthermore, satisfaction emerges as a catalyst for fostering enduring loyalty, with satisfied customers exhibiting heightened levels of both behavioral and emotional loyalty. Qualitative insights provide depth, emphasizing the emotional components of trust and the significance of perceived value in driving satisfaction. These qualitative nuances enrich the understanding of customer sentiments and experiences, complementing the quantitative findings. Implications drawn from the research underscore the strategic imperatives for BNI Bank and the broader banking industry. Embracing transparent communication, personalized service delivery, and cultivating emotional connections stand as pivotal strategies to fortify trust, elevate satisfaction levels, and foster lasting loyalty.